Polymer package biological destruction at conditions approximated to natural - Rymovskaya, Mariya V.; Ratkevich, Maksim V.; Grebenchikova, Irina A.; Sergievich, Denis S. (Journal of the Belarusian State University. Ecology, 2022)
Modern systems for the separate waste collection and recycling are not able to efficiently process all packaging materials in the composition of municipal solid waste, in particular, thin-walled products made from non-biodegradable polymeric materials. Reducing the share of such packaging and even refusing it has been enshrined in laws, it leads to development of new materials for these purposes, adequate criteria and methods for establishing biodegradability. The biodegradability of packaging material, consisting of starch, polylactide, and polyester of terephthalic acid, has been evaluated under conditions close to natural - in soil and in an aqueous environment. Packaging material degrades faster in an aqueous medium, biodegradation is more active in the presence of peptides, and mechanical destruction is faster achieved by alternating moistening with drying. Bacterial cultures had played the leading role in biodegradation, while cultures of microscopic fungi were practically not detected. This fact can be associated with the effect of photoinactivation of reactive oxygen species on the titanium oxide surface.
Keywords: biodegradable package; polymer material; biodegradation; microbiota; aquatic environment; soil